2023
DOI: 10.1021/acs.organomet.3c00278
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnesium-Hydride Complexes with Alkylene-Bridged Bis(β-diketiminate) Ligands

Abstract: Three magnesium-hydride complexes (3a−c) supported by alkylene-bridged bis(β-diketiminate) ligands have been synthesized by reacting the respective dinuclear magnesium bis(trimethylsilyl)amide complexes 1a−c with phenylsilane; 3a can alternatively be accessed by the same reaction but starting from the dinuclear magnesium n-butyl complex 2a. Single-crystal X-ray diffraction revealed a dimeric structure in the solid state, with inter-and intramolecular μ 2 -hydrides bridging the magnesium centers. The properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 49 Related species have recently been documented from Kretschmer's group. 50 Previously we showed that 1a reacts with two equiv. CO by a deoxygenative pathway leading to the formation of a coordinated acetaldehyde enolate.…”
Section: Resultsmentioning
confidence: 98%
“… 49 Related species have recently been documented from Kretschmer's group. 50 Previously we showed that 1a reacts with two equiv. CO by a deoxygenative pathway leading to the formation of a coordinated acetaldehyde enolate.…”
Section: Resultsmentioning
confidence: 98%
“…82 An alternative route to ionic hydride complexes [ 67 ][Al(OC(CF 3 ) 3 ) 4 ] and [ 68 ][Al(OC(CF 3 ) 3 ) 4 ] from [BDI Dipp Mg⋯C 6 D 6 ][Al(OC(CF 3 ) 3 ) 4 ] has also been presented by Hill and co-workers. 83 Joining two β-diketiminate ligands through appropriate alkyl or aryl N , N -linkers has been exploited by the research groups of Harder and Kretschmer to access 69 , 75 70 74 and 74 , 84 and 71–73 , 85 respectively. A fused β-oxo-δ-diiminate ligand was recently used to gain entry to a tetranuclear magnesium( ii ) hydride complex ( 75 ) which contains a rare example of a four-coordinate hydride ligand in a near square planar geometry.…”
Section: Group 2 Hydride Complexesmentioning
confidence: 99%
“…[14][15][16] The tetrametallic magnesium hydride cluster 1 was originally reported by Harder and co-workers, related species have recently been reported by Kretschmer and coworkers. [17][18][19] Reaction of 1 with CO (1 atm. 60 °C) led to selective formation of 2 (Figure 2a).…”
mentioning
confidence: 99%